2023
DOI: 10.3390/nu15081862
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus Probiotics Improve Vaginal Dysbiosis in Asymptomatic Women

Abstract: Vaginal dysbiosis can lead to serious infections in asymptomatic women. Lactobacillus probiotics (LBPs) are being investigated as a promising therapy for reversing vaginal microbiota dysbiosis. This study aimed to investigate whether administering LBPs could improve vaginal dysbiosis and facilitate the colonization of Lactobacillus species in asymptomatic women. 36 asymptomatic women were classified based on the Nugent score as Low-NS (n = 26) and High-NS (n = 10) groups. A combination of Lactobacillus acidoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Recently, we found asymptomatic BV improved with the treatment of three Lactobacillus spp. combination probiotics [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we found asymptomatic BV improved with the treatment of three Lactobacillus spp. combination probiotics [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such probiotic interventions might potentially yield favorable results among infertile individuals, particularly those with RIF. However, despite the promising implications of probiotics’ influence on vaginal health derived from studies [ 24 , 25 , 26 ], their direct impact on enhancing reproductive success remains inconclusive [ 27 , 28 , 29 ]. A randomized controlled trial involving 340 infertile women undergoing frozen embryo transfer and divided into a study group (receiving daily intravaginal lactobacilli tablets for six days) and a control group (no probiotic supplementation) demonstrated comparable biochemical and clinical pregnancy rates between the groups, with a notable reduction in the miscarriage rate within the study group [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…colonization in vagina. Ansari et al 138 Oral Total 89 women diagnosed with bacterial vaginosis and 93 women diagnosed with vulvovaginal candidiasis (VVC) All patients were treated with oral or vaginal probiotic capsules, or placebo capsules for 3 months. BV patients received L. crispatus DSM32717 and L. crispatus DSM32720.…”
Section: Dual-channel Probiotic Therapy: a Promising Approach For Add...mentioning
confidence: 99%
“…Their findings revealed that 42.9% of patients in the probiotic group exhibited negative GBS colonization in the vagina, compared to 18.0% in the placebo group, suggesting that oral probiotics could diminish pathogen colonization in the vagina 137 . Moreover, oral administration of L. acidophilus CBT LA1, L. rhamnosus CBT LR5, and L. reuteri CBT LU4 significantly improved vaginal dysbiosis in asymptomatic women and restored the abundance of Lactobacillus spp., resulting in a healthier vaginal microenvironment post-treatment 138 . Additionally, a study investigating probiotic supplementation for bacterial vaginosis and vulvovaginal candidiasis (VVC) demonstrated similar efficacy.…”
Section: Evaluating the Efficacy Of Current Probiotic Therapy In ...mentioning
confidence: 99%